2012
DOI: 10.3327/taesj.j11.040
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Release to Stagnant Water in Fukushima-1 Nuclear Power Plant

Abstract: After the severe accident in the Fukushima 1 nuclear power plant, a large amount of contaminated stagnant water has been produced in turbine buildings and surrounding areas. This rapid communication reports the calculation of the radionuclide inventory in the core, the collection of the measured inventory in the stagnant water, and the estimation of the radionuclide release ratios from the core to the stagnant water. The present evaluation is based on data obtained before June 3, 2011. It was revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 3 publications
3
31
0
Order By: Relevance
“…Similar study has been already published [11] and showed almost the same tendencies in radioactive quantities in the accumulated water as the present study. However, small differences in the ratios of I-131 and Cs-137 quantities in the accumulated water to each core inventory were found between the previous and present Table 6.…”
Section: Comparison With Previous Studysupporting
confidence: 80%
“…Similar study has been already published [11] and showed almost the same tendencies in radioactive quantities in the accumulated water as the present study. However, small differences in the ratios of I-131 and Cs-137 quantities in the accumulated water to each core inventory were found between the previous and present Table 6.…”
Section: Comparison With Previous Studysupporting
confidence: 80%
“…This is far below the Maximum Contaminant Level (MCL) of 3 H for drinking water, a limit of 740 Bq/L issued by the U.S. Environmental Protection Agency (2000). The 137 Cs concentrations are much higher than those of 3 H at almost all stations, because of the substantially higher amounts of 137 Cs produced in the damaged reactors of the F1-NPP compared to 3 H (Nishihara et al, 2015). High 3 H concentrations were found close to the shore.…”
Section: H and 137 Cs Concentrations In Surface Seawatermentioning
confidence: 86%
“…An initial 137 Cs/ 90 Sr ratio of 39 ± 1 in seawater was measured 30-600 km seaward of the FDNPPs in June 2011, which is significantly higher than the global atmospheric fallout ratio of 1.6 but closer to the 137 Cs/ 90 Sr ratio of 12.5 measured in stagnant water at the FDNPP site (average core release ratio from Nishihara et al 2012). 137 Cs/ 90 Sr ratios decreased with time, averaging 3.8 in 2013 in waters within 100 km of the FDNPP site (Castrillejo et al 2015).…”
Section: Wwwannualreviewsorg • Fukushima Daiichi and The Ocean 177mentioning
confidence: 99%